Childhood disadvantage and adolescent socioemotional wellbeing as predictors of future parenting behaviour. (January 2021) - McAnally, H.M.; Iosua, E.; Sligo, J.L.; Belsky, J.; Spry, E.; Letcher, P.; Macdonald, J.A.; Thomson, K.C.; Olsson, C.A.; Williams, S.; McGee, R.; Bolton, A.E.; et al.
Abstract: Introduction: In extending work on early life antecedents of parenting, we investigate associations between childhood family history of disadvantage, adolescent socioemotional wellbeing, and age at first parenthood and subsequent parenting behaviour. Methods: Parent-child interactions were recorded when participants in the longitudinal Dunedin Multidisciplinary Health and Development Study (New Zealand) had a three-year-old child. Data were available for 358 mothers and 321 fathers, aged between 17.7 and 41.5 at the time of their child's birth. Associations between parenting and antecedent data on socioeconomic disadvantage, adolescent wellbeing and mental health, as well as current adult mental health and age at parenting, were tested for using structural equation modelling. Results: Family disadvantage in childhood and lower adolescent wellbeing was associated with less positive future parenting, but only adult (not adolescent) anxiety/depression symptoms were directly associated with parenting behaviour. Childhood family disadvantage was associated with further disadvantage across the life course that included less positive parenting of the next generation. In contrast, socioemotional wellbeing during adolescence and later age of onset of parenting were associated with more positive parenting. Conclusions: Reducing childhood disadvantage and improving socioemotional wellbeing during childhood and adolescence is likely to have intergenerational benefits through better parenting of the next generation.